2019
DOI: 10.3126/jcmc.v9i3.25785
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Job Satisfaction among Nurses Working in Teaching Hospital, Chitwan, Nepal

Abstract: Background: Job satisfaction is a major factor in nurse retention and the de­livery of high quality care. Hence, aim of this study was to find out the factors affecting job satisfaction among nurses working in the teaching hospital, Chit­wan. Methods: A descriptive, cross-sectional research design was used and a total 135 nurses who were working for at least 3 months in the Chitwan Medical Teaching Hospital were taken as study sample. Simple random sampling tech­nique was used to select the desired sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The present study revealed that only half (50.4%) of the nurses are satisfied with their job which is similar with other studies conducted by Poudel 8 and Gyang 9 in which 57.85% and 64.8% were satisfied respectively. This might be due to common issues related to salaries and staff welfare they have faced.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study revealed that only half (50.4%) of the nurses are satisfied with their job which is similar with other studies conducted by Poudel 8 and Gyang 9 in which 57.85% and 64.8% were satisfied respectively. This might be due to common issues related to salaries and staff welfare they have faced.…”
Section: Discussionsupporting
confidence: 90%
“…Level of satisfaction was categorized based on mean score. 15 Ethical approval was taken from institutional review committee of Manipal College of Medical Science (Ref no-MEMG/ IRC/359/GA). Prior to data collection verbal permission was obtained from the participants.…”
Section: Methodsmentioning
confidence: 99%